28.6k views
1 vote
In problem solve the given differential equation by underdetermined coefficients y''-2y+y=xe^x

User Rducom
by
5.4k points

1 Answer

2 votes

Answer:

Solution is
y(t)=C_1e^x+C_2xe^x+(x^3e^x)/(6)

Explanation:

Given Differential Equation,


y ...............(1)

We need to solve the given differential equations using undetermined coefficients.

Let the solution of the given differential equation is made up of two parts. one complimentary solution and one is particular solution.


\implies\:y(x)=y_c(x)+y_p(x)

For Complimentary solution,

Auxiliary equation is as follows

m² - 2m + 1 = 0

( m - 1 )² = 0

m = 1 , 1

So,


y_c(x)=C_1e^x+c_2xe^x

Now for particular solution,

let
y_p(x)=Ax^3e^x


y'=Ax^3e^x+3Ax^2e^x


y

Now putting these values in (1), we get


Ax^3e^x+6Ae^2e^x+6Axe^x-2(Ax^3e^x+3Ax^2e^x)+Ax^3e^x=xe^x


Ax^3e^x+6Ae^2e^x+6Axe^x-2Ax^3e^x-6Ax^2e^x+Ax^3e^x=xe^x


6Axe^x=xe^x


6A=1


A=(1)/(6)


\implies\:y_p(x)=(x^3e^x)/(6)

Therefore, Solution is
y(t)=C_1e^x+C_2xe^x+(x^3e^x)/(6)

User Ian Moote
by
5.6k points